Mechanical properties and microstructural investigation of polypropylene/exfoliated graphite nanoplatelets/ nano-magnesium oxide composites - I. Alateyah, A; H. Latief, F (International Journal of Engineering and Technology, 2018)
Polypropylene/exfoliated graphite nanoplatelets composites reinforced with a low concentration of nano-magnesia have been successfully fabricated, using injection molding machine. The mechanical properties and microstructure of the composites were investigated, in the present study. The XRD patterns of the composites showed the peaks of xGnP and n-MgO, where the intensity of the xGnP peaks became stronger with increasing the concentration of xGnP added into polypropylene matrix. In addition, the SEM micrographs revealed a good dispersion of fillers within the matrix. The results showed that increasing the amount of exfoliated graphite nanoplatelets up to 10 wt. % resulted in increasing the composite flexural strength, flexural modulus, and hardness up to 35% and 91%, 6.7%, respectively, compared to the monolithic polypropylene.